Web reasoning and rule systems 6th International Conference, RR 2012, Vienna, Austria, September 10-12, 2012. Proceedings - Straccia, Umberto; Krotzsch, Markus (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 6th International Conference on Web Reasoning and Rule Systems, RR 2012, held in Vienna, Austria, in September 2012. The 27 revised research papers, presented together with 2 invited talks and 5 research summaries were carefully reviewed and selected from 42 submissions. The papers were organized in topical sections on technical communications, algorithms, design aspects of rule markup, design of ontology languages, engineering of engines, translators, and other tools, standardization efforts, such as the Rules Interchange Format activity at W3C, and applications.